IMPLEMENTATION OF WORK DISCIPLINE IN IMPROVING PERFORMANCE OF KARAWANG STATE COURT EMPLOYEES CLASS 1 B - Hana Febrianti; Nandang; Zenita Apriani (Institute of Computer Science (IOCS), 2022)
The Karawang District Court is a general judicial environment under the Supreme Court of the Republic of Indonesia as the executor of independent judicial powers to administer justice in upholding Law and Justice, the Karawang District Court as the